Breaking Free of Class Constraints—A Qualitative Study of 10 Post-80s Rural Children with Higher Educational Attainment. Issue 5 (2nd November 2019) - Yonggui, Dong
Abstract: This study selected 10 rural children who attended undergraduate programs at 211/985 universities as its research subjects, for analysis of the underlying reasons behind their achievement of higher educational attainment. The study found that the principal reasons were as follows: First, escaping a rural area and repaying their parents were powerful motivations for them to study hard. Second, they exhibited a high degree of identification with the instrumental value of education: they believed that knowledge would change their fate, and assiduously studied to achieve this end. Third, they played an active role, proactively competing for all available resources. Fourth, as important others, teachers compensated for the inadequacy of their families' cultural capital.